Andean mountain building did not preclude dispersal of lowland Epiphytic orchids in the Neotropics. - Pérez-Escobar, O; Gottschling, M; Chomicki, G; Condamine, F; Klitgård, B; Pansarin, E; Gerlach, G (Springer Nature, 2017)
The Andean uplift is one of the major orographic events in the New World and has impacted considerably the diversification of numerous Neotropical lineages. Despite its importance for biogeography, the specific role of mountain ranges as a dispersal barrier between South and Central American lowland plant lineages is still poorly understood. The swan orchids (Cycnoches) comprise ca 34 epiphytic species distributed in lowland and pre-montane forests of Central and South America. Here, we study the historical biogeography of Cycnoches to better understand the impact of the Andean uplift on the diversification of Neotropical lowland plant lineages. Using novel molecular sequences (five nuclear and plastid regions) and twelve biogeographic models, we infer that the most recent common ancestor of Cycnoches originated in Amazonia ca 5 Mya. The first colonization of Central America occurred from a direct migration event from Amazonia, and multiple bidirectional trans-Andean migrations between Amazonia and Central America took place subsequently. Notably, these rare biological exchanges occurred well after major mountain building periods. The Andes have limited plant migration, yet it has seldom allowed episodic gene exchange of lowland epiphyte lineages such as orchids with great potential for effortless dispersal because of the very light, anemochorous seeds.